Recognizing the trafficking in human beings victimization - Simeunović-Patić Biljana (Temida)
In spite of relative prevalence of trafficking in human beings issues in the expert and general public discourse in recent years, recognition of victimization by various specialists that may come across with victims still is being estimated as unsatisfactory. Stereotypes about victims of trafficking in human beings are just one factor that imperils correct and prompt recognition of victims, i.e. victims' identification, as principal prerequisite of their protection and support. Today, there are various efforts to overcome that problem - primarily through the training of professionals and creating the identification guidelines, i.e. lists of indicators of trafficking in human beings victimization; however, these resolves only one part of the problem and reveal some new challenges at the same time.